Dataset on yield changes due to climate change based on Agricultural Model intercomparison and improvement project (AgMIP) Global Gridded Crop Model Intercomparison - CGIAR Research Program on Policies, Institutions, and Markets (2018)
Datasets were used for analysis. The methodology and some outputs have been published as discussion papers.